2022
DOI: 10.1042/cs20220043
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL1 attenuates cancer migration, invasion, and stemness through regulating FOXO3a-mediated SOX2 expression in colorectal cancer

Abstract: Angiopoietin-like protein 1 (ANGPTL1) is a member of the ANGPTL family that suppresses angiogenesis, cancer invasion, metastasis, and cancer progression. ANGPTL1 is down-regulated in various cancers including colorectal cancer (CRC); however, the effects and mechanisms of ANGPTL1 on liver metastasis and cancer stemness in CRC are poorly understood. In the present study, we identified that ANGPTL1 was down-regulated in CRC and inversely correlated with metastasis and poor clinical outcomes in CRC patients form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Fan et al reported that ANGPTL1-positive expression was negatively associated with tumor size, lymph node metastasis, and TNM stage, and poor prognosis of CRC patients [ 15 ]. In the present article, the author supported the above findings through the ONCOMINE database analysis and Human Tissue Microarray staining [ 4 ]. Above findings made ANGPTL1 more attractive either as cancer prognostic or predictive biomarkers.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Fan et al reported that ANGPTL1-positive expression was negatively associated with tumor size, lymph node metastasis, and TNM stage, and poor prognosis of CRC patients [ 15 ]. In the present article, the author supported the above findings through the ONCOMINE database analysis and Human Tissue Microarray staining [ 4 ]. Above findings made ANGPTL1 more attractive either as cancer prognostic or predictive biomarkers.…”
supporting
confidence: 62%
“…Nowadays, several target genes and signaling pathways involved in CRC metastasis have been elucidated, but none was selected as an effective treatment target [ 3 ]. In this issue of Clinical Science [ 4 ], Chang et al demonstrated the effects of angiopoietin-like protein 1 (ANGPTL1) on CRC, as they found that increased ANGPTL1 expression was associated with less metastasis and better clinical outcomes. What is more, Forkhead box O-3a (Foxo3a)–SRY-related HMG-box-2 (Sox2) axis was first explored as the mechanism of ANGPTL1 regulated cancer migration, invasion, and stemness.…”
mentioning
confidence: 99%
“…AARS2 and FOXO3 are protective factors in the prognostic model of CRC, and the former regulates the proliferation of colorectal cancer by affecting mitochondrial respiration [ 32 ]. The latter is associated with morbidity and mortality in CRC [ 33 ] and can modulate its mediated SOX2 expression to affect cancer migration, invasion, and stem cell proliferation [ 34 ]. ATF4 regulates tumor autophagy in CRC and affects tumor survival [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Te precise mechanism of CRC liver metastasis has yet to be determined. CSCs play an important role in primary tumor initiation, development, and metastasis [21]. Many regulators of CSCs have been found to be involved in CRC liver metastasis [22][23][24].…”
Section: Discussionmentioning
confidence: 99%